Spatial organization of enzymes to enhance synthetic pathways in microbial chassis: a systematic review - Xin-yuan Qiu; Si-Si Xie; Lu Min; Xiao-Min Wu; Lv-Yun Zhu; Lingyun Zhu (Microbial Cell Factories, 2018)
Abstract For years, microbes have been widely applied as chassis in the construction of synthetic metabolic pathways. However, the lack of in vivo enzyme clustering of heterologous metabolic pathways in these organisms often results in low local concentrations of enzymes and substrates, leading to a low productive efficacy. In recent years, multiple methods have been applied to the construction of small metabolic clusters by spatial organization of heterologous metabolic enzymes. These methods mainly focused on using engineered molecules to bring the enzymes into close proximity via different interaction mechanisms among proteins and nucleotides and have been applied in various heterologous pathways with different degrees of success while facing numerous challenges. In this paper, we mainly reviewed some of those notable advances in designing and creating approaches to achieve spatial organization using different intermolecular interactions. Current challenges and future aspects in the further application of such approaches are also discussed in this paper.